(untitled) (Mediscope, 2025)
Background: Pancytopenia is a hematological condition characterized by the simultaneous reduction of red blood cells, white blood cells and platelets, presenting a wide differential diagnosis. Objective: This study aimed to analyze the clinical profile and etiological spectrum of pancytopenia patients admitted to the Medicine department of Khulna Medical College Hospital. Methods: This observational study was conducted in the Department of Medicine at Khulna Medical College Hospital (KMCH), Khulna, Bangladesh, from December 2013 to May 2014. A total of 50 patients with pancytopenia were enrolled through purposive sampling. Patients underwent thorough evaluations including clinical assessments, laboratory investigations and bone marrow examinations. All Statistical analyses were performed using the Statistical Package for the Social Sciences (SPSS) software (version 17). Results: In this study, aplastic anemia emerged as the most prevalent cause, affecting 56% of patients, followed by megaloblastic anemia (18%), hypersplenism (10%), and malaria (8%). Clinical manifestations primarily included pallor, fatigue, fever and bleeding with significant variations in hematological parameters. Statistical analyses revealed significant differences in absolute neutrophil count (p-value<0.05) and mean corpuscular volume (p-value<0.05) among the various cases. Conclusion: This study underscores the importance of a comprehensive diagnostic approach to pancytopenia, highlighting regional variations in its etiologies and calling for further investigations to delineate local factors influencing this condition. Mediscope 2025;12(2): 60-65